Opportunities for market intelligence to inform discussion on TPP refinements - Donovan, Jason; Gitonga, Agnes; Muungani, Dean; Coaldrake, Peter; Mbugua, Mercy; Demont, Matty; Gbegbelegbe, Sika; Rutsaert, Pieter; Naziri, Diego (CGIAR Initiative on Market Intelligence, 2024)
This article explores the role of market intelligence in refining Target Product Profiles (TPPs) for seed products. Since 2022, over 250 TPPs have been developed as blueprints for seed products, capturing essential traits for farmers, processors, and consumers. The article discusses the importance of integrating market intelligence to ensure that TPP designs reflect actual market needs, as opposed to assumptions. It emphasizes the value of TPPs as a standard in product design, advocating for increased involvement of stakeholders such as researchers, seed companies, and national agricultural systems to improve the relevance and effectiveness of breeding programs.